Implementasi Pemanfaatan Media Visual untuk Keterampilan Berbicara pada Pembelajaran Bahasa Arab - Thufeyl Vandayo; Danial Hilmi (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2020)
This research discusses visual media as an Arabic learning instrument that concentrates on speaking skills. Visual media is a popular medium in the education era 4.0 by the millennial generation. Through a literature review, the research describes important points in the use of visual media: the category of visual media, the principles of using visual media, guidelines in designing visual media and their implementation in Arabic learning. The purpose of using visual media is to increase students' enthusiasm for learning and increase teacher innovation and creativity in teaching. Some visual media that teachers can use in the learning process of Arabic speaking skills include: wall clocks, bulletin boards, flannel boards, posters and pictures. The concepts and principles of using visual media need to be considered, so that the process of using visual media in learning is effective and optimal.